2006
DOI: 10.1007/s00268-005-0791-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Positron Emission Tomography with Fluorine‐18‐Fluorodeoxyglucose is Predictive of Prognosis in Patients with Hepatocellular Carcinoma after Resection

Abstract: The SUV ratio was related significantly to disease-related death as well as other predictive factors, including the number of tumors, the size, stage, and involvement of vessels, and the involvement of the capsule. Consequently, we conclude that the SUV ratio provides information of prognostic relevance in patients with HCC before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 26 publications
6
102
0
Order By: Relevance
“…For analyzing accuracy in the detection of small tumors or extrahepatic metastases, we prospectively enrolled more patients who had modified UICC stage I, II, and IVb, compared with the patient population of our previous report (27). A high rate of positive findings on 18 F-FDG PET has been reported in patients with elevated serum a-fetoprotein levels (7) and in patients with poorly differentiated HCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…For analyzing accuracy in the detection of small tumors or extrahepatic metastases, we prospectively enrolled more patients who had modified UICC stage I, II, and IVb, compared with the patient population of our previous report (27). A high rate of positive findings on 18 F-FDG PET has been reported in patients with elevated serum a-fetoprotein levels (7) and in patients with poorly differentiated HCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in HCC, several investigators have reported that 18 F-FDG uptake evaluated by preoperative PET scan is associated with tumor differentiation as well as recurrences and survival after resection or transplantation. [14][15][16][17] Hence, it is feasible that 18 F-FDG uptake on PET scan, like size and number criterion, might be an important prognostic factor in the establishment of treatment and surveillance plans. However, most studies on HCC and 18 F-FDG-PET have focused primarily on either tumor detection in preoperative settings or prognostic value in patients treated with resection or transplantations.…”
mentioning
confidence: 99%
“…However, some reports have indicated that a high FDG uptake reflects malignant potential in HCC (22,23). In the present case, the 4 th segment tumor had higher FDG uptake than the other tumors.…”
Section: Discussionmentioning
confidence: 99%